Pendampingan Pengelolaan Sampah Menuju Desa Peduli Sampah di Desa Semanu Kabupaten Gunung Kidul - Alia Ariesta; Okka Adiyanto; Utaminingsih Linarti; Isana Arum Primasari; Endah Utami; Gita Indah Budiarti; Ika Dyah Kumalasari; Titisari Juwitaningtyas (Empower : Jurnal Pengembangan Masyarakat Islam, 2021)
Waste management is an important thing that needs to be resolved. The accumulation of garbage and the not yet managed urban and rural waste are one of the driving factors for this community service. Desa Semanu is one of the villages that already has a TPS-3R in Gunung Kidul Regency but the TPS-3R has not been utilized optimally. This study uses a qualitative method with community empowerment program. Aims for this research is to know the implementation of community empowerment programs. Furthermore, the purpose community service is to make Desa Semanu into a village that cares about waste by taking advantage of the integration of TPS 3R and a waste bank. One of the activities that have been carried out to support a village that cares about waste is by providing counseling about the dangers of burning waste to the environment and health. In addition, there was also counseling on the assistance of the Ahmad Dahlan University Center of Energy and Environmental Studies to make Desa Semanu can make a Waste Care Village. Based on the evaluation that has been carried out, most of the extension participants have increased their knowledge of solid waste knowledge.